2020
DOI: 10.3389/fphar.2020.00784
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the Efficacy of Artemisinin–Piperaquine in the Treatment of Uncomplicated Plasmodium falciparum Malaria Among Children Under 5 Years of Age in Est-Mono District, Togo, in 2017

Abstract: Background: Malaria is a major public health concern in Togo. The Est-Mono district of Togo has a population of 150,000. Accordingly,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…A retrospective longitudinal study using PNLP routine data from 2008 to 2017, showed an average annual increase in malaria cases in children under five of + 13.1%, also with strong heterogeneity ranging from + 6.3% in the Lomé Commune region to + 16.7% in the Centrale region [ 7 ]. Several other studies on malaria in Togo have focused on the clinical management of cases [ 8 , 9 ], the evolution of malaria incidence [ 7 ], the evaluation of the implementation of malaria control interventions [ 10 , 11 ], clinical trials on malaria vector resistance to insecticides [ 29 , 30 ] and socio-cultural factors [ 12 ]. So far, there are very few studies examining the risk factors associated with regional heterogeneity in malaria prevalence among children under five in Togo using national population-based survey data [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective longitudinal study using PNLP routine data from 2008 to 2017, showed an average annual increase in malaria cases in children under five of + 13.1%, also with strong heterogeneity ranging from + 6.3% in the Lomé Commune region to + 16.7% in the Centrale region [ 7 ]. Several other studies on malaria in Togo have focused on the clinical management of cases [ 8 , 9 ], the evolution of malaria incidence [ 7 ], the evaluation of the implementation of malaria control interventions [ 10 , 11 ], clinical trials on malaria vector resistance to insecticides [ 29 , 30 ] and socio-cultural factors [ 12 ]. So far, there are very few studies examining the risk factors associated with regional heterogeneity in malaria prevalence among children under five in Togo using national population-based survey data [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial search found 45 relevant articles published between 2000 and 2020, of which 9 reported repetitive data. After screening for titles, 38 abstracts, and 15 full-text reviewed, 5 studies reporting RCTs ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ; Onasanya et al., 2015 ), and 2 reporting a noncomparative single-arm studies ( Deng et al., 2008 ; Wang et al., 2020 ) were included for the analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, one was published in the Chinese language ( Deng et al., 2008 ) and others in the English language ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ; Onasanya et al., 2015 ; Wang et al., 2020 ). Four of the five RCTs ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ) and the two single-arm studies ( Deng et al., 2008 ; Wang et al., 2020 ) reported PCR-confirmed cure rate on day 28, while one trial reported the same on day 42 ( Onasanya et al., 2015 ). A total of 917 participants were included in the experiment, including 145 in the single-arm study, 335 in the AP group, 188 in the DHP group, 25 in the ASAM group, 59 in the ASAQ group, and 165 in the AL group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study could not examine risk factors that could explain this heterogeneity of malaria prevalence in children under ve in Togo. Several studies on malaria in Togo have focused on the clinical management of cases (8, 9), the evolution of malaria incidence ( 7), the evaluation of the implementation of malaria control interventions (10,11), clinical trials on malaria vector resistance to insecticides (29, 30) and socio-cultural factors (12). So far, there are very few studies examining the risk factors associated with regional heterogeneity in malaria prevalence among children under ve in Togo using national population-based survey data (7).…”
mentioning
confidence: 99%